Implementation of the Tanos Application at PT Pelindo Daya Sejahtera, East Java Regional Office - Nathania Chika Aprilia Kristin; Indah Prabawati; Tjitjik Rahaju; Tauran T (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to analyze the implementation of the TANOS application as a digital attendance system for outsourced workers at PT Pelindo Daya Sejahtera Regional East Java. The study employed a qualitative descriptive approach. Data were collected through interviews, observation, documentation, and literature review. The analysis was conducted using George C. Edward III’s policy implementation model, which consists of communication, resources, disposition, and bureaucratic structure. The findings reveal that the implementation of TANOS has supported the digital transformation of attendance administration by improving attendance monitoring, discipline control, and data management efficiency. Communication was carried out through socialization and coordination among implementers and users. Resource support was reflected in the availability of information technology personnel, digital infrastructure, and system integration with MyPDS. The disposition of implementers showed a positive commitment toward policy implementation, while the bureaucratic structure was supported by company regulations and internal coordination mechanisms. However, several challenges remain, including user adaptation and technical constraints related to system operation. Therefore, continuous system improvement and periodic evaluation are necessary to enhance the effectiveness and sustainability of TANOS implementation.